Research is Tentative, but That's Okay: Overcoming Misconceptions about Scientific Tentativeness through Refutation Texts. Issue 1 (2nd January 2020) - Flemming, Danny; Kimmerle, Joachim; Cress, Ulrike; Sinatra, Gale M.
ABSTRACT: Prior research from the field of science communication shows that, upon reading journalistic articles about novel scientific findings, readers who recognize the tentative nature of the findings rate the journalistic article that reports these findings as less credible. Apparently, readers' appraisal is influenced by misconceptions about the relationship of text credibility and the tentativeness of research findings. In four experimental studies ( N = 301; N = 481; N = 68; N = 69) to test how this negative association might be overcome, we used different settings (online, laboratory), various samples (American, German), and different scientific topics (Deep Brain Stimulation, hypnotherapy, oceanic plastic pollution). We provided participants either with a refutation text that confronted the misjudgment of scientific tentativeness or with a control text. Refutation texts supported people in overcoming these misconceptions and even affected their behavior. Our results contribute to closing the gap between science communication and education, and carry important implications for practical implementation and further research.